Clinical application of MIIRMR as a salvage method in gadolinium-enhanced MRI after intra-tympanic injection. (1st April 2022) - Huang, Jianjian; Tang, Cheng; Xia, Wei; Feng, Yiwei; Tan, Songhua; Xie, Lihong; Jiang, Muliang; Qin, Yuhong; Zhang, Huiting; Tang, Anzhou
Abstract: Background: Three-dimensional fluid-attenuated inversion-recovery (3 D-FLAIR) and real inversion-recovery (3 D-real IR) sequences are used to detect endolymphatic hydrops (EH), but medium inversion-time inversion-recovery imaging with magnitude reconstruction (MIIRMR) may be more sensitive. Aims: We investigated the inner-ear visualisation success rate and EH detection rates of 3 D-FLAIR and 3 D-real IR, and whether salvage MIIRMR could improve EH detection. Materials and Methods: Fifty-one patients (102 ears) with episodic or chronic vestibular syndrome were injected intra-tympanically with 8-fold diluted gadolinium, and 3 D-FLAIR and 3 D-real IR images obtained 24-h post-injection. If 3 D-FLAIR inner-ear visualisation failed, additional MIIRMR was performed. The success and EH detection rate increase by MIIRMR was calculated. The diagnostic performance of combined MIIRMR + 3D-FLAIR + 3D-real IR for Meniere's disease (MD) was evaluated. Results: The success rates of 3 D-FLAIR and 3 D-real IR were 88.90% and 72.55%, respectively. MIIRMR increased the success and EH detection rates by 11.10% and 6.86%, respectively. In MD, MIIRMR increased these rates by 10.53% and 10.53%, respectively. 3 D-FLAIR + 3D-real IR + MIIRMR had 92.11% sensitivity, 79.68% specificity, 72.92% positive-predictive value, and 94.44% negative-predictive value for MD diagnosis. Conclusion and significance: MIIRMR can improve success and EH detection rates when 3 D-FLAIR fails. Combined MIIRMR + 3D-FLAIR + 3D-real IR is more valuable for diagnosing MD than conventional sequences.